2015
DOI: 10.1371/journal.pone.0138381
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ARF6 in Biliary Atresia

Abstract: Background & AimsAltered extrahepatic bile ducts, gut, and cardiovascular anomalies constitute the variable phenotype of biliary atresia (BA).MethodsTo identify potential susceptibility loci, Caucasian children, normal (controls) and with BA (cases) at two US centers were compared at >550000 SNP loci. Systems biology analysis was carried out on the data. In order to validate a key gene identified in the analysis, biliary morphogenesis was evaluated in 2-5-day post-fertilization zebrafish embryos after morpholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 70 publications
(89 reference statements)
0
73
2
1
Order By: Relevance
“…The role of the EGFR/Notch1 pathway should be confirmed in human liver as well as its applicability during embryonic liver development. Recently, the EGFR/guanine nucleotide exchange factor 100 (GEF100)/ADP‐ribosylation factor 6 (Arf6) signaling pathway has been envisaged as a regulator of intrahepatic biliary morphogenesis in a zebrafish model . Arf6 knockdown or pharmacological inhibition of EGFR in zebrafish embryo resulted in poor bile duct development.…”
Section: Erbb Receptors In Cholangiocyte Physiologymentioning
confidence: 99%
“…The role of the EGFR/Notch1 pathway should be confirmed in human liver as well as its applicability during embryonic liver development. Recently, the EGFR/guanine nucleotide exchange factor 100 (GEF100)/ADP‐ribosylation factor 6 (Arf6) signaling pathway has been envisaged as a regulator of intrahepatic biliary morphogenesis in a zebrafish model . Arf6 knockdown or pharmacological inhibition of EGFR in zebrafish embryo resulted in poor bile duct development.…”
Section: Erbb Receptors In Cholangiocyte Physiologymentioning
confidence: 99%
“…As hepatocytes seem unaffected in snapc4 mutants, indicating that the function of Snapc4 is specific to biliary cells. In many of these studies, live imaging of GFP-expressing biliary cells in cultured livers or in embryos provided invaluable insights into cell behaviors driving this dynamic morphogenetic process (Lorent et al, 2004; Ningappa et al, 2015). …”
Section: Liver Development: Zebrafish As a Paradigmmentioning
confidence: 99%
“…A recent study in zebrafish found that only depletion of add3 caused biliary devects similar to BA, prioritizing ADD3 as a BA susceptibility gene over XPNPEP1 (Tang et al, 2016). Another study of Caucasian BA cases identified a susceptibility locus on human chromosome 14q21.3, including the ARF6 gene (Ningappa et al, 2015). The two zebrafish homologs, arf6a and arf6b are expressed in the liver and knock down experiments showed they are required for early biliary development.…”
Section: Liver Development: Zebrafish As a Paradigmmentioning
confidence: 99%
“…Excessive Hedgehog activation has also been observed in children with BA [30], suggesting that Hedgehog signaling has evolutionarily conserved roles in cholangiocyte development. The Sindhi group knocked down a different candidate gene, ADP-ribosylation factor 6 ( arf6 ), which encodes a GTP-binding protein [31]. They observed similar intrahepatic biliary defects to those seen in gpc1 and add3 knockdown larvae.…”
Section: Zebrafish Models Of Liver Diseasesmentioning
confidence: 99%
“…The main challenge for the follow-up studies of patient GWAS is to determine which variants are indeed causative. Four groups have used zebrafish to validate GWAS variants in BA patients, as well as in patients with elevated liver enzyme levels [28, 98, 31, 29]. Furthermore, CRISPR/Cas9-mediated targeted mutagenesis can now be applied in zebrafish not only to generate null mutations, but also to precisely recapitulate the same mutations found in patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%